Ethics-related Legal Amendments and Ethics Applications for Medical Research - BABA, Shunsuke; TODA, Isumi (Journal of Japanese Society of Oral Implantology, 2019)
Laws and guidelines relating to ethics are now being issued by the government nearly every year. Not only do dental professionals conducting clinical research have to comply with an increasing number of regulations ; they must first gather a large amount of information to store as knowledge. Since the scope of application of the "Ethics Guidelines for Epidemiological Research" (revised in 2007) and the "Ethical Guidelines for Clinical Research" (revised in 2008)─both issued by the Ministry of Health, Labour and Welfare and the Ministry of Education, Culture, Sports, Science and Technology─was considered difficult to interpret, the guidelines were integrated into the "Ethical Guidelines for Medical and Health Research Involving Human Subjects," which have been in effect since 2015. Following their enforcement, with the recent full-fledged implementation of the updated Act on the Protection of Personal Information, which clarifies the scope of personal information and provides for its legitimate distribution, these guidelines have also been revised to ensure proper handling of personal information in research, and came into effect on May 30, 2017. In recent years, several such new or revised ethical laws and guidelines have been implemented. Obviously, non-compliance is not an option, so a realistic outlook of the facts is necessary to prevent researchers from abandoning research in dejection. It is therefore essential to grasp the background of the strengthened regulations and understand their purpose and requirements. An ethics training conference known as the "Ethics Committee Seminar," hosted by the Japanese Society of Oral Implantology, was relaunched as the "Ethics Seminar on Medical Research" in response to the overwhelmingly rapid revision of guidelines and to attempt to disseminate information. In addition to imparting an understanding of the original ethical guidelines, the announced purpose of this seminar is to explain what kind of research requires an ethics review in this academic society and, for research and case reports that require it, how to apply to the ethics review committee. However, because of the large number of members, it is difficult to provide ethics review training to everyone. Since members still perceive a lack of clarity in ethics applications, this article explains the essence of medical ethics and provides commentary on details of the latest amendments in ethics regulations, as well as ways of creating research ethics applications to help members understand what kind of academic research requires an ethics review.